A first screening of chytrid fungus Batrachochytrium in amphibians in French zoos. Issue 1 (25th March 2019) - Marquis, O.; Miaud, C.; Gibault, C.; Chai, N.
Abstract : Batrachochytrium dendrobatidis ( Bd ) and Batrachochytrium salamandrivorans ( Bsal ) screening was carried out in captive amphibians in order to establish the presence of these fungal pathogens in French zoos. Over a period of 3 years, 437 skin swabs were collected at eight French zoos and one private breeding centre [38 species of Anura, 7 species and 2 subspecies of Urodela (salamanders and newts), and 1 caecilian species] and these were analysed using qPCR. None of the samples revealed the presence of Bsal . Bd was detected four times on three species – American bullfrog Lithobates catesbeianus, Common midwife toad Alytes obstetricans and Yellow‐bellied toad Bombina variegata – all of which originated from or were in contact with the natural environment. Abstract : Batrachochytrium dendrobatidis ( Bd ) and Batrachochytrium salamandrivorans ( Bsal ) screening was carried out in captive amphibians in order to establish the presence of these fungal pathogens in French zoos. Over a period of 3 years, 437 skin swabs were collected at eight French zoos and one private breeding centre [38 species of Anura, 7 species and 2 subspecies of Urodela (salamanders and newts), and 1 caecilian species] and these were analysed using qPCR. None of the samples revealed the presence of Bsal . Bd was detected four times on three species, all of which originated from or were in contact with the natural environment. (Photo: Mallorcan midwife toad Alytes muletensis . F.‐G. Grandin, MNHN)